The Role of Government in Social Welfare: A Bibliometric Analysis of Policy Development, Evaluation, and Social Impacts - Achmad Zahruddin; Adit Mohammad Aziz; Herni Ramayanti; Andika Isma; Ratna Dewi (West Science Social and Humanities Studies, 2023)
The ecological stability of our world and human well-being are dependent on biodiversity, but in the age of climate change, biodiversity faces hitherto unheard-of difficulties. This study investigates the intricate interactions between the preservation of biodiversity and the effects of climate change in Indonesia's rural Sukabumi District. Using a mixed-methods approach that includes field observations, interviews, surveys, and secondary data analysis, the study looks into the drivers of biodiversity loss as well as the state of biodiversity now and the effects of climate change on regional ecosystems. The findings show the incredible biodiversity of Sukabumi District, including its healthy coral reefs and terrestrial rainforests, as well as the noticeable effects of climate change, such as altered species behavior and coastal erosion. Unsustainable land-use practices and climate-related variables are identified as major contributors to the decline of biodiversity. Community-led conservation efforts provide success stories, but to protect biodiversity and improve climate resilience, strong policy proposals are required. The suggested recommendations place a strong emphasis on multi-stakeholder collaboration, conservation education, climate resilience, sustainable land-use practices, and community engagement. Sukabumi District is highlighted in the report as a microcosm of the problems facing biodiversity conservation worldwide, and it calls for swift and coordinated action to save nature's final line of defense against climate disaster.